Bandgap Engineering of Graphene Nanoribbons by Control over Structural Distortion - Hu, Yunbin; Xie, Peng; De Corato, Marzio; Ruini, Alice; Zhao, Shen; Meggendorfer, Felix; Straaso, Lasse Arnt; Rondin, Loic; Simon, Patrick; Li, Juan; Finley, Jonathan J.; Hansen, Michael Ryan; et al. (Journal of the American Chemical Society, 2018)
Among organic electronic materials, graphene nanoribbons (GNRs) offer extraordinary versatility as next-generation semiconducting materials for nanoelectronics and optoelectronics due to their tunable properties, including charge-carrier mobility, optical absorption, and electronic bandgap, which are uniquely defined by their chemical structures. Although planar GNRs have been predominantly considered until now, nonplanarity can be an additional parameter to modulate their properties without changing the aromatic core. Herein, we report theoretical and experimental studies on two GNR structures with "cove"-type edges, having an identical aromatic core but with alkyl side chains at different peripheral positions. The theoretical results indicate that installment of alkyl chains at the innermost positions of the "cove"-type edges can "bend" the peripheral rings of the GNR through steric repulsion between aromatic protons and the introduced alkyl chains. This structural distortion is theoretically predicted to reduce the bandgap by up to 0.27 eV, which is corroborated by experimental comparison of thus synthesized planar and nonplanar GNRs through UV-vis-near-infrared absorption and photoluminescence excitation spectroscopy. Our results extend the possibility of engineering GNR properties, adding subtle structural distortion as a distinct and potentially highly versatile parameter.
CRIS-Team Scopus Importer:2023-03-20